Karyological Investigation on Seven Centaurea L. (Asteraceae) Taxa from Turkey - Tasar, Neslihan; Dogan, Gulden; Kiran, Yasar (Univ Tokyo Cytologia, 2018)
The somatic chromosome numbers and karyotypes were examined in seven species of genus Centaurea L. distributed in Turkey. The chromosome numbers were determined as 2n=2x=16 in C. behen L. and C. solstitialis L.; 2n=2x=18 in C. cynarocephala Wagenitz and C. agregata Fisch. & Mey. ex DC. ssp. agregata; 2n=2x=20 in C. iberica Trev. ex Sprengel; 2n=2x=26 in C. balsamita Lam.; 2n=4x=36 in C. virgata Lam. All of the chromosomes had centromeres at median point (M), median region (m), and submedian region (sm). Satellite chromosomes (sat-chromosomes) were observed only in C. virgata. The findings for each of the analyzed taxa are compared each other and with the results of previous studies.
Keywords: Asteraceae; Centaurea; Chromosome number; Karyotype; Turkey